المدائح النبوية في الشعر الشعبي الجزائري - حني, عبد اللطيف (Revues faculté des lettres et des langues, 2014)
يسعى هذا المقال إلى دراسة ظاهرة لطالما لاحظناها تتردد في الشعر الشعبي الجزائري ألا وهي المدائح النبوية، فقد نظم أغلب الشعراء الشعبيين في هذا الموضوع المرتبط بالدين الإسلامي، محاولين كشف النزعة الدينية في الشعر الشعبي الجزائري وارتباطه بها في جل موضوعات النظم والتفصيل في موضوعات المدائح النبوية وجمالياتها الفنية والتعبيرية التي عبر من خلالها الشعراء على حبهم لشخص النبي )ص)   This contribution attempts to study the phenomenon for as long as we have noted hesitate to folk poetry Algerian namely praise of the Prophet, was organized by most popular poets in this issue associated with the religion of Islam, trying to detect the tendency of religious folk poetry Algerian linked to it in most of the topics of systems and detail on the themes of praise of the Prophet aesthetic art The expression that through which poets love for a person of the Prophet